Pelatihan Komputer dan Penggunaan Microsoft Word Pada Siswa Berkebutuhan Khusus Di Homeschooling Lantaburo Kabupaten Tangerang - Muhaimin Hasanudin; Muhammad Rifqi; Ifan Prihandi (Madani : Indonesian Journal of Civil Society, 2023)
Homeschooling (HS) Lantaburo is one of the alternative schools in the city of Tangerang which has a target of fostering and developing life skills for Students with Special Needs (ABK) so they can meet the basic needs of Activity of Daily Living (ADL) so that one day they can be independent and empowered in society. In implementing the ADL program, there are obstacles, namely the difficulty of keeping up with advances in computer technology as a medium for supporting the learning of ABK students. Based on these problems, this community service aims to introduce ABK students to operating computers and teach them how to use Microsoft Word features that can be used to learn typing and others. The method used is hands-on training on basic introduction to computers and Microsoft Word applications. Of the 26 students with special needs at HS Lantaburo who were given the opportunity by the teacher to take part in the training, there were 3 students namely Autism, Dyslexia, and Down Syndrome (DS) due to limited computer equipment and training time. The context of the training is based on the participant's ability to answer every question posed in the training, starting from managing text, fonts, data storage, etc. Meanwhile, making tables still requires frequent practice. The results of the training were that Autism and Dyslexia student participants had the same range of intelligence so they could follow the training well compared to DS participants. This can be seen from the results of the evaluation carried out after the training activities. ABK students can improve their ability to operate computer equipment and Microsoft Word software, including the ability to type, edit, and format documents. Increase motivation to study, more confidence and independent in operating computers and MS Word applications.